Lipoma of Anterior Plica of Palatine Tonsil: A Case Report - Berkiten, Güler; Bal, Muhlis; Topaloğlu, İlhan; Kamalı, Gülçin (Fırat University, 2012)
Lipomatous tumors represent an infrequent cause for upper aerodigestive tract neoplasms, specially concerning the palatine tonsils, that should be included in their differential diagnosis. A case of palatine tonsil anterior plica lipoma in a 17 year-old girl is reported with the available literatüre.

Lipomatöz tümörler, üst sindirim sistemi tümörleri arasında ayrıcı tanıda her ne kadar akılda tutulması gerekliyse de bu tümörler nadir olup özellikle palatin tonsillerde daha nadir görülür. 17 yaşında palatin tonsil ön plikada lipomu olan bayan hastamızı literatür verileriyle sunduk.
Tonsil Ön Plika Lipomu: Olgu Sunumu